Advanced High-Resolution Tomography in Regenerative Medicine Three-Dimensional Exploration into the Interactions between Tissues, Cells, and Biomaterials (Fundamental Biomedical Technologies, 2018)
This book covers the state-of-the-art research on advanced high-resolution tomography, exploring its role in regenerative medicine. and also explores the 3D interactions between tissues, cells, and biomaterials. Various multidisciplinary paths in regenerative medicine are covered, including X-ray microtomography and its role in regenerative medicine, synchrotron radiation-based microtomography and phase contrast tomography, the challenge of the vascularization of regenerated tissues, lung and cartilage imaging, and more. This is an ideal book for biomedical engineers, biologists, physicists, clinicians, and students who want to pursue their studies in the field of regenerative medicine. This book also: Reviews in detail the algorithms and software used for the 3D exploration of regenerated tissue Covers the latest research on the use of X-ray microtomography for muscle diseases Details applications of synchrotron radiation tomography in orthopedics and dentistry.